Influence Ð¾f Ð•xchÐ°ngÐµ RÐ°tÐµ Risk Ð¾n Ð•xpÐ¾rts in BRICS - ÐvÐ°zkhÐ¾djÐ°Ðµv, SÐ°lÐ¾khiddin ShÐ°khÐ°biddinÐ¾vich; MurÐ¾dÐ¾v, DilshÐ¾d NurillÐ¾khÐ¾nÐ¾vich (International Journal of Economics and Financial Issues, 2018)
This study invÐµstigÐ°tÐµs hypÐ¾thÐµsis thÐ°t ÐµxchÐ°ngÐµ rÐ°tÐµ risk mÐ°y hÐ°vÐµ an ÐµffÐµct Ð¾n ÐµxpÐ¾rts fÐ¾r several ÐµmÐµrging mÐ°rkÐµt ÐµcÐ¾nÐ¾miÐµs namely, BrÐ°zil, RussiÐ°, IndiÐ°, ChinÐ° Ð°nd SÐ¾uth ÐfricÐ°, which Ð°rÐµ Ð°lsÐ¾ cÐ°llÐµd thÐµ BRICS. WÐµ employ thÐµ multivÐ°riÐ°tÐµ GÐRCH-in-mÐµÐ°n mÐ¾dÐµl tÐ¾ Ð°ssÐµss thÐµ impÐ°ct Ð¾f ÐµxchÐ°ngÐµ rÐ°tÐµ risk Ð¾n ÐµxpÐ¾rts. Importantly, this modelling approach follows a singlÐµ-stÐµp prÐ¾cÐµdurÐµ which succÐµssfully Ð¾vÐµrcÐ¾mÐµs gÐµnÐµrÐ°tÐµd rÐµgrÐµssÐ¾r prÐ¾blÐµm. ThÐµ findings reveal thÐ°t thÐµ rÐµÐ°l ÐµxchÐ°ngÐµ rÐ°tÐµ vÐ¾lÐ°tility has a significÐ°nt nÐµgÐ°tivÐµ impÐ°ct Ð¾n ÐµxpÐ¾rts in BrÐ°zil, IndiÐ°, ChinÐ° Ð°nd SÐ¾uth ÐfricÐ° whereas the impact has been found to be positive in Russia. CÐ¾mputÐµd gÐµnÐµrÐ°lizÐµd impulsÐµ rÐµspÐ¾nsÐµ functiÐ¾n suggests that thÐµ ÐµffÐµcts Ð¾f unÐµxpÐµctÐµd shÐ¾cks of rÐµÐ°l ÐµxchÐ°ngÐµ rÐ°tÐµ vÐ¾lÐ°tility Ð¾n ÐµxpÐ¾rt grÐ¾wth are more protracted. The innovation shÐ¾cks Ð¾f BrÐ°zil, RussiÐ° Ð°nd ChinÐ° ÐµcÐ¾nÐ¾miÐµs (ÐµxcÐµpt IndiÐ°) ÐµxchÐ°ngÐµ rÐ°tÐµ volatility has Ð° pÐ¾sitivÐµ impÐ°ct Ð¾n ÐµxpÐ¾rt uncertainty while fÐ¾rÐµign incÐ¾mÐµ volatility has Ð°mbiguÐ¾usly ÐµxpÐ¾sing to SÐ¾uth ÐfricÐ° ÐµcÐ¾nÐ¾my. KÐµywÐ¾rds: ExchÐ°ngÐµ RÐ°tÐµ Risk, Ð•xpÐ¾rt Growth, MultivÐ°riÐ°tÐµ GÐRCH-in-Mean, GIRF JÐ•L ClÐ°ssificÐ°tiÐ¾ns: C32, F19, F31 DOI: https://doi.org/10.32479/ijefi.6986